Automatic Railway Gate System for Commuter Line Train Based on Sensor Accelerometer and Microcontroller - Erna Kusuma Wati (Faktor Exacta, 2022)
The design of the automatic system of crossbar gates has been done a lot to reduce the number of accidents at the railroad crossing, but no one has been tested directly when the real train passes. In this study will design an automatic system of railroad crossing gates that will be tested on the passing KRL commuter trains so that they can display the vibration acceleration data. There are two systems in this study; system 1 is a vibration detector, and system two is an automatic system at the railway gate. The Accelerometer sensor is a passing train vibration detector, and Arduino UNO will give the command or control of the train gate to open and close automatically with a servo motor and turn on the LED and Buzzer. The system test is carried out when ten commuter line trains cross the train line on the Jakarta-Depok, Indonesia route on each variation of distance. Variations in the interval between system 1 to system two namely 200m, 450m, and 650m are performed to obtain the time difference between the railroad gates closing entirely and the time when the train passes at the gate crossing, which is close to the standard time. The test results at a distance of 200 meters have a time difference of 2.9 seconds with an average value of 10.01 m / s2, at a distance of 450 meters for 14.1 seconds; g 10.01 m / s2, and at a range of 650 for 36.7 seconds the value of g is 10.02 m / s2. Thus the results of research on the design of an automatic system based on the accelerometer and microcontroller railroad gates placed with the distance between the systems as far as 650 meters can be recommended to PT. Commuter Indonesia makes all railroad crossing gate systems work automatically and to improve road safety and safety at railroad crossings..